Não por ser humana, mas por ser mulher: questões de gênero em Midnight Sun (2020), de Stephenie Meyer, uma leitura política - Lumini, Julia Leite (Universidade Federal de São Carlos, 2026)
This dissertation analyzes the novel Midnight Sun (2020), by the North American author Stephenie Meyer, through a political reading of the literary text, as proposed by Fredric Jameson (1992) and Ferreira (2018). The central objective of this research is to investigate how patriarchalism structures the romantic relationships depicted in the novel, considering the perspective of the narrator Edward Cullen. To this end, it is necessary to historicize Midnight Sun (2020) and situate it within the field of Young Adult literature, consolidated in the mid-twentieth century and aimed at an adolescent readership, traditionally associated with themes such as identity, love, and belonging. As a specific objective, the study seeks to demonstrate how the narrative figures gender inequality and a system of male domination in contemporaneity, understanding these elements as constitutive of the social and cultural formation of the United States, which has been marked by patriarchal values since its period of consolidation. Methodologically, the research is grounded in Anglo-American feminist criticism, particularly drawing on the contributions of Elaine Showalter (1997), articulated with Jameson’s (1992) contemporary dialectical criticism, with the aim of identifying the North American Political Unconscious as figured in the novel. As a contribution, this study seeks to expand the debate on gender and twenty-first-century North American literature, as well as to reinforce the critical legitimacy of Young Adult literature as an object of academic investigation.
Not because she is human, but because she is a woman: gender issues in Midnight Sun (2020) by Stephenie Meyer, a political reading
Keywords: Crepúsculo; Literatura young adult; Stephenie Meyer; Sol da meia-noite; Midnight sun; Twilight; Young adult literature; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS; 5. Igualdade de Gênero